Evaluating charcoal producers’ preferences for improved production systems in Marigat sub county, Baringo County - Siko, I.; Sola, P.; Mulwa, R.; Otieno, P. (Elsevier, 2021)
Many households in Kenya depend on charcoal as an important source of energy. However, overharvesting of trees and the use of inefficient technologies promote unsustainable charcoal production. Furthermore, high demand for charcoal from slow-growing indigenous species contributes to increased pressure in the drylands, threatening future supply and livelihoods. Recent studies have shown that Prosopis juliflora an invasive species introduced to arrest desertification equally produces quality charcoal. Also, improved technologies with more efficient carbonization rates have the potential to reduce not only the number of trees harvested but also quality of charcoal. Despite the existence of improved technologies, and the presence of fast-growing Prosopis juliflora, charcoal production remains unsustainable in Baringo County. This study used choice experiments (CE) to determine charcoal producers willingness to pay (WTP) for improved charcoal production system in Marigat sub-county.The attributes measured include charcoal quality, wood quality, P.juliflora growth trend and kiln type. Primary data was collected from a sample of 384 randomly selected charcoal producers using a semi-structured questionnaire. Study results indicate that charcoal producers were willing to pay more charcoal quality improvement which is associated with improved production systems and quality wood. However, they were not willing to pay for improved kilns. The findings suggest that the charcoal producers have a natural inclination to improved technologies with the study recommending charcoal producer association (CPA) membership as the first and efficient point of contact to adopt and use improved technologies.